Transformation of Parental Supervision in Reducing LGBT Risk in Banda Aceh City: Analysis of The Concept of Muraqabah and Hadhanah - Nasir, Qanita; Sa'dan, Saifuddin; Achyar, Gamal (Sakina: Journal of Family Studies, 2026)
This research analyzes the phenomenon of sexual deviance (LGBT) in Banda Aceh City, which emerged as a consequence of shifting social values driven by globalization and the penetration of unfiltered digital technology. Despite the formal implementation of Islamic Law, Banda Aceh City, as an urban hub and higher education center, has experienced a weakening of communal social control, providing space for clandestine communities. The primary objective of this study is to dissect the role of parenting and the effectiveness of parental supervision in protecting adolescent morality from the perspectives of both Islamic and positive law. Utilizing a qualitative field research methodology, primary data were gathered through in-depth interviews with parents residing in Banda Aceh City. The findings reveal that parental supervision in this region is categorized into two distinct typologies: direct physical supervision through the enforcement of a strict 10:00 PM curfew for co-residing families, and digitally mediated supervision for migrant children that prioritizes deep emotional bonding. Empirically, the internalization of the muraqabah concept a transcendental awareness of divine supervision has proven to be a more effective internal control mechanism for maintaining a child's natural disposition (fitrah) compared to mere physical monitoring. These results confirm that strengthening family functions through the holistic principles of guidance, affection, and nurturing (asah, asih, asuh) serves as the fundamental preventive instrument in safeguarding the moral integrity and dignity of children amidst contemporary global challenges. <!--a=1-->